(untitled) (Global Journal of Science Frontier Research, 2016)
In this paper we deal with non-smooth multi criteria optimization problem Throughout the text we consider the functions which are non-differentiable A few special derivatives have been deployed to obtain first order optimality conditions We presented the generalized form of optimality conditions for multi-objective optimization problem when classical derivatives failed to apply We illustrate these optimality conditions by means of suitable examples